OBESITY IN SEVERE ASTHMA: UNVEILING CHALLENGES AND EXPLORING NEW THERAPEUTIC OPTIONS (International journal of medical sciences, 2025)
Background. Obesity has emerged as one of the most prevalent comorbidities in severe asthma, affecting up to half of patients in some severe asthma cohorts and profoundly modifying disease expression, treatment response and prognosis.Objective. This narrative review summarizes current evidence on the epidemiology and pathobiology of obesity-associated severe asthma, highlights diagnostic and therapeutic challenges, and discusses emerging pharmacologic and non-pharmacologic strategies with a focus on weight-targeted interventions.Methods. A non-systematic literature search of PubMed, Scopus and Web of Science was performed for English-language publications from 2010 to November 2025 using terms including severe asthma, obesity, obese asthma, GLP-1 receptor agonists and bariatric surgery. Key guidelines, large observational cohorts, randomized controlled trials, meta-analyses and high-impact narrative reviews were prioritized.Results. Obesity increases the risk of developing asthma and is over-represented in severe asthma phenotypes. Obese individuals with severe asthma exhibit distinct clinical and inflammatory features, including poorer symptom control, more frequent exacerbations, reduced quality of life, altered lung mechanics and a greater burden of comorbidities. Systemic low-grade inflammation, adipokine imbalance, mechanical constraints, metabolic dysregulation and microbiome alterations contribute to a complex “obese asthma” endotype that is often T2-low and relatively corticosteroid-resistant. Established interventions—structured lifestyle modification and bariatric surgery—can substantially improve asthma control, lung function and quality of life in selected patients. Emerging data suggest that glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and other anti-obesity pharmacotherapies may confer additional benefits beyond weight loss, potentially reducing exacerbations and improving asthma control in obese individuals.Conclusion. Obesity in severe asthma represents a distinct, heterogeneous and therapeutically challenging endotype. Optimal management requires a treatable-traits framework that integrates aggressive weight management, optimization of inhaled and biologic therapy, and targeted use of novel anti-obesity agents. High-quality phenotype-driven trials are needed to define which patients derive the greatest benefit from specific weight-centred interventions.